Time‐Resolved Orientation and Phase Analysis of Lead Halide Perovskite Film Annealing Probed by In Situ GIWAXS. Issue 14 (3rd April 2022) - Reus, Manuel A.; Reb, Lennart K.; Weinzierl, Alexander F.; Weindl, Christian L.; Guo, Renjun; Xiao, Tianxiao; Schwartzkopf, Matthias; Chumakov, Andrei; Roth, Stephan V.; Müller‐Buschbaum, Peter
Abstract: Scalable thin‐film deposition methods are increasingly important for hybrid lead halide perovskite thin films. Understanding the structure evolution during non‐equilibrium processes helps to find suitable materials and processing parameters to produce films with well‐performing optoelectronic properties. Here, spin‐cast and slot‐die coated bilayers of lead iodide (PbI2 ) and methylammonium iodide (MAI) are investigated by in situ grazing‐incidence wide‐angle X‐ray scattering during the thermal annealing process, which converts the bilayer into methylammonium lead iodide (MAPI). Photoluminescence (PL) and UV/Vis measurements show increasing crystallinity during the annealing process and a slight PL red‐shift of the spin‐cast film, attributed to crystallite coalescence that is not prominent for the slot‐die coated film. The disintegration of the solvent‐precursor complex (MA)2 (Pb3 I8 ) ⋅ 2 DMSO and conversion into perovskite are followed in situ and differences in the morphology and time evolution are observed. In both, spin‐cast and slot‐die coated thin‐films, the isotropic orientation is dominant, however, in the slot‐die coated films, the perovskite crystallites have an additional face‐on orientation ((110) parallel to substrate) that is not detected in spin‐cast films. An Avrami model is applied for the perovskite crystal growth that indicates reduced dimensionality of the growth for the printed thin films. Abstract : In this work in situ morphology analysis during the MAPI perovskite annealing process of spin‐cast and slot‐die coated thin films is coupled with optical measurements that show a slightly larger bandgap for spin‐cast films. Morphology is probed by in situ GIWAXS and reveals an additional face‐on crystallite orientation in the slot‐die coated films that grow stronger during the annealing.